Mechanisms influencing the lateral roof roadway deformation by mining-induced fault population activation: a case study. (2016) - Wang, Feng; Xu, Jialin; Xie, Jianlin; Li, Zhu; Guo, Jiekai
Mining-induced fault population activation often leads to dynamic disasters. It is of considerable significance to understand the strata movement and mining-induced stress evolution induced by fault population activation. This paper studied the movement and rotation of the roof strata which are influenced by a complex interaction between two faults in its strike direction of panel 31100 of no. 1 mine in Pingdingshan, China. Protective coal pillars for the lateral roof roadway were designed to be wide enough in case of eliminating fault disturbance. Severe roadway deformation was also observed throughout advancing. Based on the deformation observation of roadways, a structural instability model of considering the fault population was established. Moreover, mining-induced stress distribution and lateral roof roadway deformation mechanisms during fault population activation were investigated by both theoretical analysis and 3D numerical simulations. According to the mining-induced stress distribution, the sliding instability of roof strata above the working face aggravated the structural rotation of the lateral strata. Intense stress concentration induced by lateral roof rotation resulted in lateral roof roadway deformation. As concerning the effect of fault population activation, results obtained are of great importance for reasonable allocation of working face and roadways, and also for the prevention of dynamic disasters. [Received: February 5, 2015; Accepted: July 20, 2015]